Quality control of chest radiograph procedure - Santinun , Jaruwan; Jivapong , Supawan; Jamroonsai, Somluck (The Thai Journal of Radiological Technology, 2023)
Chest radiography, also known as a chest x-ray. The images show the internal organs of the chest and neighboring structures. A chest radiograph which an X-ray beam enters behind the patient and exits the front of patient to an anterior image receptor, known as the Posteroanterior (PA) and X-ray beam passes from anterior the patient to the image receptor behind, known as the Anteroposterior (AP), is the most common radiological investigation for diagnosing chest abnormalities. As a guideline to reduce the repetitive rate of x-rays, radiological technologist should have knowledge and understanding for quality control of chest radiographs. Starting from patients’ factors that come in different conditions, which requires skill and experience in the work of radiological technologist to assess the appropriate positioning for each case. Somes requires a method of positioning that is different from the routine from the textbook including the factors from the radiological technologist that should be known to adjust the various parameters of the X-ray machine in order to provide the appropriate radiation dose from different positions in each patient. Additionally, the process of evaluating whether the obtained photographs are sufficient quality for the radiologist to report the accurately results. The factors to control the quality of chest radiographs should begin from the process of patient preparation, positioning, X-ray machine parameters setting and post image processing from the software of the x-ray machine to be accurately. If the radiological technologist does not have accurate knowledge of chest radiographs, this may cause in the radiologist receive improper image, resulting in inaccurate or unclear report affecting recipients to lose the opportunity to receive the correct diagnosis. Therefore, it is necessary to have standards to have quality control of chest radiographs before sending the images to the PACs system for radiologist’s report.